2021
DOI: 10.3389/fevo.2021.698885
|View full text |Cite
|
Sign up to set email alerts
|

Within-Species Trait Variation Can Lead to Size Limitations in Seed Dispersal of Small-Fruited Plants

Abstract: The inability of small-gaped animals to consume very large fruits may limit seed dispersal of the respective plants. This has often been shown for large-fruited plant species that remain poorly dispersed when large-gaped animal species are lost due to anthropogenic pressure. Little is known about whether gape-size limitations similarly influence seed dispersal of small-fruited plant species that can show a large variation in fruit size within species. In this study, fruit sizes of 15 plant species were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…In a second scenario, we tested if the animal community can keep up the effectiveness of seed dispersal when one of the four common disperser species goes extinct, and the remaining community compensates the reduced fruit removal (i.e., interaction compensation of extinct species). Our simulations showed that animals would be fully able to quantitatively compensate the interactions of lost dispersers in the IPM, because morphological mismatches between plants and their dispersers rarely occur at the species-level in small-fruited plants 76 , 77 .…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In a second scenario, we tested if the animal community can keep up the effectiveness of seed dispersal when one of the four common disperser species goes extinct, and the remaining community compensates the reduced fruit removal (i.e., interaction compensation of extinct species). Our simulations showed that animals would be fully able to quantitatively compensate the interactions of lost dispersers in the IPM, because morphological mismatches between plants and their dispersers rarely occur at the species-level in small-fruited plants 76 , 77 .…”
Section: Resultsmentioning
confidence: 87%
“…In addition, before species are lost, the environment has changed in its structure and with it the effectiveness of ecological interactions 15 , 87 . Therefore, dietary preferences of animals and cryptic functional loss of interactions, rather than morphological mismatches 76 , can be expected to limit the ability of the remaining species to compensate interactions after the loss of common species in our study system. Moreover, the loss of certain animals could affect population processes that are beyond the scope of this study, for instance range expansion 32 , 88 , gene flow 89 , and plant migration in response to climate change 17 , 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, medium-sized seeds were cached more frequently across all treatments. The reason for preferences for medium-sized seeds may be that for a small granivore the largest acorns might be inconvenient to handle or simply too large to carry due to gape limitation (Muñoz and Bonal 2008;Rehling et al 2021). Moreover, granivores face a trade-off between energetic benefits and handling time that rises with seed size (Muñoz and Bonal 2008;Stephens and Krebs 2019), which may lead to preference for harvesting and caching of medium-sized seeds rather than large and small ones (Wang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the large‐scale variability in reproductive trait expression might already trace these recently established anthropogenic gradients. It has been hypothesized that fragmented landscapes accumulate phenotypes with lower dispersal ability (Riba et al, 2009), which is often linked to larger seed and fruit sizes (Rehling et al, 2021). Transferred to plant communities, we hypothesize that the proportions of plant fruit types and dispersal strategies predictably change depending on the degree of current land use and the existing dispersal barriers like agricultural areas, forest fragments, or road traffic infrastructure.…”
Section: Introductionmentioning
confidence: 99%